Targeting motifs in frustule-associated proteins from the centric diatom Thalassiosira pseudonana - Fattorini, Neri; Maier, Uwe G. (Frontiers in Plant Science, 2022)
The frustule of diatoms has an exceptional structure composed of inorganic and organic molecules. In the organic fraction, protein families were identified whose members are expected to have a complex cellular targeting to their final location within the frustule. Here we investigated for frustule-targeting signals two representatives of the cingulin family, the proteins CinY2 and CinW2; beside an already known, canonical signal peptide, we have identified further regions involved in cellular targeting. By using these regions as a search criteria we were able to identify two new frustule proteins. In addition, we showed that temporal expression determines the final localization of one cingulin. Our results therefore point to a sophisticated cellular and extracellular targeting of frustule components to build the fascinating frustule structure of a diatom.